2002
DOI: 10.1111/j.1749-6632.2002.tb04485.x
|View full text |Cite
|
Sign up to set email alerts
|

WE‐14, a Chromogranin A‐Derived Neuropeptide

Abstract: The neuropeptide WE-14 is derived from the posttranslational processing of chromogranin A (CgA). While CgA is expressed in a preponderance of neuroendocrine cells, WE-14 is generated in a distinct subpopulation of CgA-immunopositive cells, most notably in the adrenal, pituitary, and parathyroid glands. Physiological and pharmacological studies have demonstrated that CgA is cleaved to generate WE-14 in the adrenal chromaffin cell population and in the enterochromaffin-like (ECL) cells of the oxyntic mucosa. Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Peptide antigen mimotopes for these T cells, identified here, and in previous studies 11,12 , shared a common amino acid motif in the predicted p5 to p9 portion of the peptides [WX(R/K)M(D/E)], which suggested that the ChgA amino acid (aa) sequence 354–362 (EDKR WSRMD ) was the probable antigenic epitope. Surprisingly, peptides containing this sequence did not activate the T cells, but the clones were activated by an overlapping peptide, WE14 (aa 359–372, WSRMD QLAKELTAE), a natural cleavage product of ChgA 13 . This finding was quite unexpected, because despite the presence of the antigen motif, the stimulating WE14 peptide lacked the N-terminal amino acids that would occupy positions p1 to p4 of the I-A g7 peptide-binding groove and are normally important for stable MHC class II binding.…”
mentioning
confidence: 99%
“…Peptide antigen mimotopes for these T cells, identified here, and in previous studies 11,12 , shared a common amino acid motif in the predicted p5 to p9 portion of the peptides [WX(R/K)M(D/E)], which suggested that the ChgA amino acid (aa) sequence 354–362 (EDKR WSRMD ) was the probable antigenic epitope. Surprisingly, peptides containing this sequence did not activate the T cells, but the clones were activated by an overlapping peptide, WE14 (aa 359–372, WSRMD QLAKELTAE), a natural cleavage product of ChgA 13 . This finding was quite unexpected, because despite the presence of the antigen motif, the stimulating WE14 peptide lacked the N-terminal amino acids that would occupy positions p1 to p4 of the I-A g7 peptide-binding groove and are normally important for stable MHC class II binding.…”
mentioning
confidence: 99%
“…Screening of all HPLC fractions with MALDI-TOF MS and comparing the masses of the ions with the calculated masses of predicted FLP and NLP peptides resulted in the identification of 75 C. elegans peptides, 37 of which were also detected in the first peptidomic study of C. elegans using 2D-nano-LC-QTOF MS/MS [20]. These peptides eluted from 23% to 37% CH 3 CN (fraction [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. To determine the identity of ion peaks that could correspond to more than one peptide with the same monoisotopic mass, the remaining part of the corresponding HPLC fractions was also subjected to nano-LC-QTOF MS/MS in order to obtain sequence data.…”
Section: Identification Of 75 Neuropeptides By Off-line Hplc Maldi-tomentioning
confidence: 99%
“…16.4.3.5 Chromogranin A A number of peptides were identified that correspond to the C-terminal region of chromogranin A, which contains multiple pairs of basic amino acids that are potential sites for cleavage by PC1 and PC2. Chromogranin A, which also belongs to the family of the granins, is considered to be a multifunctional prohormone that is subject to selective proteolysis in distinct neuroendocrine cell populations [41]. WE-14 [41], together with the C-terminal sequence, AYGFRDPGPQL of the mouse ortholog of the bovine peptide called catestatin were detected.…”
Section: Secretogranin IIImentioning
confidence: 99%
See 1 more Smart Citation
“…It is generated in a subpopulation of adult rat neuroendocrine cells (Curry et al, 1991) and to varying degrees in human neuroendocrine neoplasia (Gleeson et al, 1996;Heaney et al, 2000). Developmental studies have shown that WE-14 is generated at an early stage of endocrine gland generation in the rat and pig (Barkatullah et al, 1997(Barkatullah et al, , 2001 and that it has an ancient lineage (Curry et al, 2002).…”
Section: Introductionmentioning
confidence: 99%